2021
DOI: 10.1155/2021/1730594
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Multicriteria Decision-Making Analysis of Agricultural Product Logistics in Agricultural Economic Management

Abstract: The purpose is to establish a logistics supplier evaluation and selection model for green supply chain, which can effectively take into account the environmental problems, while the enterprise economy is developing. The logistics supplier evaluation index system is established under the background of green logistics based on fuzzy theory and multicriteria decision-making theory. The green competitiveness index is innovatively introduced into the system. Moreover, a fuzzy hybrid multicriteria decision-making me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The deterministic global optimization method proposed by Tang and Wang is strict in mathematical theory, which is suitable for relatively simple or qualitatively studied global optimization problems, and it is difficult to obtain the global optimal solution [ 11 ]. And the ant colony algorithm is easier to realize.…”
Section: Related Workmentioning
confidence: 99%
“…The deterministic global optimization method proposed by Tang and Wang is strict in mathematical theory, which is suitable for relatively simple or qualitatively studied global optimization problems, and it is difficult to obtain the global optimal solution [ 11 ]. And the ant colony algorithm is easier to realize.…”
Section: Related Workmentioning
confidence: 99%
“…The validation showed that the proposed model could predict the pulling effect of agricultural economic management on it. Based on fuzzy theory and multi-criteria decision theory, the literature [11] analyzes the decision of agricultural logistics objectives in agricultural economic management and constructs a green supply chain logistics supplier evaluation selection model, which has high reference value for green logistics enterprise evaluation. The literature [12] proposed to apply big data in agriculture, to mine and analyze relevant agricultural big data, and then to visualize the big data.…”
Section: Introductionmentioning
confidence: 99%